Using a Mixed-Methods Approach to Analyze Traumatic Experiences and Factors of Vulnerability Among Adolescent Victims of Bullying - Roques, Marjorie; Laimou, Dimitra; Camps, François-David; Mazoyer, Anne-Valérie; El Husseini, Mayssa’ (Frontiers in Psychiatry, 2020)
A number of studies have analyzed the bullying phenomenon among adolescent victims. Relatively few studies, however, have specifically addressed the associated post-traumatic stress disorder (PTSD). Our clinical practice and therapeutic encounters with adolescents reveal that the majority of bullied adolescents suffer from high levels of PTSD. The objective of this study is to further explore bullied adolescents’ traumatic experiences. In an attempt to analyze these experiences, this article presents a mixed-methods approach. Such an approach will allow to analyze the PTSD that results from bullying as well as subjects’ psychic and family-relevant vulnerabilities. First, bullying will be defined in the context of adolescence. Then the main studies on bullying will be presented. The objectives, tools and methods of analysis will be presented. The interviews will be analyzed according to the Interpretative Phenomenological Analysis (IPA) method. Projective tools, family drawings, Rorschach and Thematic Apperception Test (TAT), will be analyzed using a psychoanalytic interpretation method. Each qualitative tool will be used alongside a validated quantitative tool. The Clinical Administered PTSD Scale (CAPS-CA-5 questionnaire) and the interviews conducted will thus allow to analyze PTSD and traumatic experiences. The Family Assessment Device (FAD) and the family drawing test will enable to assess family functioning; lastly, the Symptom Check List (SCL-90) that will be used alongside Rorschach and TAT tests will allow to analyze individual psychological vulnerabilities. This approach will increase data validity. The originality of this research study is based on a mixed-methods approach, our methodology which is based on clinical psychology, and the choice of certain research tools which have received little attention to date. Ultimately, this study may help improve how bullying is identified and could contribute toward the reinforcement or revision of the criteria that characterize bullying. Lastly, it may help us explore various unexamined dimensions of bullying. A possible limitation is the complexity associated with such a protocol.